Analysis of Parents Communication Patterns on the Childrens’ Character Building at Bukit Mega Harmoni Residence, Moncongloe Sub-District, Maros Regency - Iqbal Maliang, Muhammad; Sukmawaty, Sukmawaty; Mokoginta, Karmila (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
The parents communication patterns on the childrens’ were communication carried out by parents with children to character building. The Objectives of this study were to find out to character of children and parents communication patterns at Bukit Mega Harmony Residence, Moncongloe Sub-District, Maros Regency. The methods of this research used to descriptive approach qualitative method. This research was conduct on October 9th until 23th 2023 at Bukit Mega Harmony Residence, Moncongloe Sub-District, Maros Regency. The sample of this research were 6 parents of six childrens’ who had children aged 5 to 11 years. This research result found that there were various children's characters such as stubbornness, indifference, and resistance. They must got what they want if they don't get what they want, they were angry, cry and be impatient. Meanwhile, the parents communication patterns included high tone of voice, biting, hitting, and used a sharp gaze, but some of parents exhibited the vocal expressions of frustration or anger while engaging in communication with their children.